Transformasi dan Kolaborasi Cerdas bagi Entrepreneur Coffee Shop untuk Keunggulan Kompetitif - Kusumaningsih, Sabtarini; Rianawati, Titik (Digital Bisnis: Jurnal Publikasi Ilmu Manajemen dan E-Commerce, 2025)
In the digital era and globalization, competition in the business world is very tight, requiring entrepreneurs to always adapt to change. Business transformation and collaboration are key elements in achieving competitive advantage. One of the businesses that is currently booming and growing rapiddly is the coffee shop business. This research aims to explore how digital transformation and intelligent collaboration can help coffee shop entrepreneurs achieve competitive advantage. The approach used in this study is a qualitative descriptive approach by collecting data through in-depth interviews and observations of several coffee shop in Semarang city.the results of the study show that the application of digital technology and collaboration with creative communities can increase competitiveness, as well as the importance of adapting to changes in technology and the business environment in order to create sustainable competitive advantages.